Dicrostonyx hudsonius - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
35. Ungava Collared Lemming Dicrostonyx hudsonius French: Lemming d'Ungava / German: Ungava-Halsbandlemming / Spanish: Lemming de collar de Ungava Other common names: Labrador Collared Lemming Taxonomy. Mus hudsonius Pallas, 1778, [Labrador, Canada. This species is monotypic. Distribution. NE Canada, in N Quebec and Labrador, including Belcher and King George Is. Descriptive notes. Head—body 112-160 mm, tail 12-22 mm, hindfoot 20-25 mm; weight 40-90 g. The Ungava Collared Lemming is stocky, with relatively short limbs, short tail, small eyes, and indistinct dorsal stripe extending to rump. Pelage is seasonally dimorphic, with long white fur in winter to match snowy environments and brownish gray with buffy or rusty sides, throat, and ear tufts in summer. Venter is grayish. Poorly developed, reddish chest collar is often present. Habitat. Tundra from old beach terraces to alpine meadows up to elevations of c.1000 m. Near tree line, Ungava Collared Lemmings typically avoid wooded areas and inhabit burrows in rocky slopes and dry lichen tundra. Food and Feeding. The Ungava Collared Lemming eats grasses, berries, bark, and buds. Breeding. Ungava Collared Lemmings can breed year-round, especially during population increases, but breeding mostly occurs in spring and summer (March-September). Gestation lasts 22-26 days. Litters have 3-5 young, and females have 2-3 litters/year. Activity patterns. Ungava Collared Lemmings can be active day or night throughout the year. Movements, Home range and Social organization. Ungava Collared Lemmings are often found in small colonies. They are thought to have relatively small home ranges. Status and Conservation. Classified as Least Concern on The IUCN Red List. Bibliography. Bradley, Ammerman et al. (2014), Cassola (2016g), Fedorov & Goropashnaya (1999, 2016), Krohne (1982), Manning (1976), Rausch (1977), Rausch & Rausch (1972), Wilson & Ruff (1999). Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 ...